PERAN CAGAR BIOSFER DALAM PEMBANGUNAN BERKELANJUTAN DI JAWA TIMUR - Apriliani, Adini; Sholihah, Laili Zakiyyatus; Abidah, Khumairoh Nur; Irawanto, Rony (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Indonesia's natural resources need to be protected and preserved, because there are several things that threaten the sustainability of the ecosystem in East Java. Sustainable development cannot be separated from three things, namely economic, social, and environmental. The use of natural resources must be in harmony, in harmony, and balanced with environmental functions. This study uses a literature review method that is relevant to the cases or problems found. Internationally, it has received attention from UNESCO so that two biosphere reserves have been established in East Java, namely: CB-BTSA (Bromo Tengger Semeru Arjuno Biosphere Reserve) and CB-B (Blambangan Biosphere Reserve). Conservation in supporting sustainable development is carried out by creating ecotourism. Because the culture of each region is different and has its own uniqueness, it can support the community's economy. The development of ecotourism based on environmental management is a means of education and character development. Therefore, the concept of understanding the environment must be understood in depth so that it can be applied to various groups as a form of preserving nature